Comprehensive identification of the PEBP gene family in Vicia faba highlighting VfTFL1a variation and phenotypic insights into determinate growth - Hannah Ohm; Umer Mahmood; Jenny Östberg; Josefin Alverup; Åsa Grimberg; Per Hofvander (Scientific Reports)
Abstract The phosphatidylethanolamine binding protein (PEBP) family regulates key plant processes including growth, development, flowering, seed germination, formation, and dormancy. Despite their importance for these processes that determine agronomical important characters, PEBP genes in faba bean (Vicia faba L.) and closely related legumes remain underexplored. This study identified 11 VfPEBP genes for the first time in Vicia faba, classifying them into MFT-like, TFL-like, and FT-like subfamilies, and examining their relationships to PEBP-genes of the legumes Pisum sativum and Vicia sativa. TFL1 homologs, crucial for growth determinacy, are an important focus for breeding to achieve a more confined flowering and maturation time. Cis-element analysis suggested VfTFL1-genes are regulated by light, hormones, and abiotic stress. Amplicon sequencing of VfTFL1a, a gene linked to shoot apical meristem fate, identified novel allelic variation but none of these could discriminate determinate from indeterminate varieties, invalidating a previously reported marker. Field trials revealed that determinate varieties of faba bean flowered later but had more uniform agronomic traits compared to indeterminate ones. These findings provide new insights into the PEBP gene family, highlighting its critical role in regulating flowering time and plant architecture in Vicia faba and underscoring its potential as a target for crop improvement.